Nanomaterials in targeting amyloid-β oligomers: current advances and future directions for Alzheimer's disease diagnosis and therapy - Randhawa, Shiwani; Saini, Trilok Chand; Bathla, Manik; Bhardwaj, Rahul; Dhiman, Rubina; Acharya, Amitabha (Beilstein Journal of Nanotechnology, 2025)
The amyloid cascade hypothesis posits that amyloid-β oligomers (AβOs) are the most neurotoxic species in Alzheimer’s disease (AD). These oligomers, characterized by their high β-sheet content, have been shown to significantly disrupt cell membranes, induce local inflammation, and impair autophagy processes, which collectively contribute to neuronal loss. As such, targeting AβOs specifically, rather than solely focusing on amyloid-β fibrils (AβFs), may offer a more effective therapeutic approach for AD. Recent advances in detection and diagnosis have emphasized the importance of accurately identifying AβOs in patient samples, enhancing the potential for timely intervention. In recent years, nanomaterials (NMs) have emerged as promising agents for addressing AβOs regarding their multivalent interactions, which can more effectively detect and inhibit AβO formation. This review provides an in-depth analysis of various nanochaperones developed to target AβOs, detailing their mechanisms of action and therapeutic potential via focusing on two main strategies, namely, disruption of AβOs through direct interaction and the inhibition of AβO nucleation by binding to intermediates of the oligomerization process. Evidence from in vivo studies indicate that NMs hold promise for ameliorating AD symptoms. Additionally, the review explores the different interaction mechanisms through which nanoparticles exhibit their inhibitory effects on AβOs, providing insights into their potential for clinical application. This comprehensive overview highlights the current advancements in NM-based therapies for AD and outlines future research directions aimed at optimizing these innovative treatments.
Keywords: Alzheimer’s disease; amyloid; amyloid-β oligomers; detection; dissociation; nanomaterials